O estresse no ambiente de trabalho docente - (:unkn) unknown (Universidade Federal do Pampa, 2017)
The present study aims to bring the vision of the psychic suffering of the teaching professional, since it is perceived with certain clarity when the job stops being object of pleasure, well being and satisfaction and gives place to the suffering and the fatigue. This process is the result of the high demand with multi - functions performed by the teacher in the educational field which can make him a stressed person. For this reason, during this research we tried to identify the factors that influence the teacher to be stressed in the work environment. In the methodological path, a case study was conducted, with a qualitative-quantitative approach based on content analysis. The group who participated in the research were thirteen teachers who work in a State School of Elementary Education in the city of Hulha Negra. Teachers who have a working period of twenty, forty and sixty hours a week, in which their profession are several psychosocial stressors arising from their professional activity. The results pointed out as the main stressors in the work environmen:: indiscipline, lack of limit of the students, wage devaluation, political and social neglect of how education is treated and disorganization of the school environment. It was It can be concluded that the participants presented signs of Burnout Syndrome, due to the great crisis that public education is, such as devaluation of wages and salaries in installments, also highlights the dissatisfaction with the career and indiscipline of the students, together with the intense pace of work among others.
Keywords: Estresse; Docente; Escola; Stress; Teacher; School; CNPQ::CIENCIAS HUMANAS